How and why does the disease progress? A qualitative investigation of the transition into long-standing anorexia nervosa - Catherine Broomfield; Paul Rhodes; Stephen Touyz (Journal of Eating Disorders, 2021)
Plain English summary Anorexia nervosa (AN) is a complex illness that has the potential to develop into a long-term presentation. When this occurs, the best way of treating this stage of the disease is currently being debated with new models of care being investigated and compared to more traditional approaches to treatment. One of the difficulties in developing more effective treatment is the lack of understanding into how and why the AN illness transitions from an earlier to later stage. It was the aim of the current study to discover the changes that occur as the AN illness progresses. A total of 11 women were interviewed to discuss their experience of AN as it progressed into a long-term illness. It was discovered that across participants, five themes emerged: (a) transition, (b) trauma, (c) functionality, (d) identity, and (e) failure of current models of treatment. Possible reasons as to why current treatment approaches are not working for long-term AN are discussed. Recommendations are made for improving education for health professionals so as to reduce the trauma that is currently being experienced by some individuals with a long-standing illness.